Length‐weight relationships of four fish species from the lower reaches of the Nujiang River and its tributaries in China. (6th March 2021) - Lin, Feng; Wang, Zhibang; Luo, Zunlan; Sun, Guang; Chen, Xiaoyong
Abstract: As one of the largest Southeast Asian rivers, flowing through China, Myanmar, and Thailand, the Nujiang (Salween) River contains a unique and rich diversity of fish species. In the present study, we investigated the length–weight relationships (LWRs) of four fish species ( Pteronemacheilus meridionalis, Devario shanensis, Exostoma gaoligongense, and Glyptothorax granosus ) collected from the lower reaches of the Nujiang River and its tributaries (24.175N~25.842N, 98.861E~98.903E), including the Mengboluo, Kungong, Luomingba and Laowo rivers in southwest China. Specimens were collected by using drift gill nets (100 m length × 1.5 m depth or 3 m depth, mesh‐size: 1 cm‐5 cm), cast nets (6.5 m, mouth opening: 35 × 45 cm 2, mesh‐size: 4 mm), and an electric shocker apparatus (12 V, 200 Hz) from different regions in the Nujiang River basin in September and October 2019 and June and September 2020. Before the collected fishes were placed in formalin, standard length ( SL ) and net weight ( W ) were measured respectively to the nearest 0.1 cm and 0.1g, respectively. Based on searches of the FishBase database and other relevant scientific literature, this study provides a new record of maximum size for P . meridionalis and LWRs for the four fish species.